Beta Diversity Patterns of Post-fire Forests in Central Yunnan Plateau, Southwest China: Disturbances Intensify the Priority Effect in the Community Assembly - Han, Jie; Shen, Zehao; Li, Yiying; Luo, Caifang; Xu, Qian; Yang, Kang; Zhang, Zhiming (Frontiers in Plant Science, 2018)
Post-fire succession is an ideal case for studying effects of disturbance on community assembly, and the key is to disentangle the contributions of assembly processes to the variation of community composition, namely beta diversity, and the contingent scales. The central Yunnan Plateau of Southwest China is characterized by monsoon related seasonal drought, and frequent forest fires. We sampled five fire sites burned in different years and a middle aged forest, measured species composition dissimilarity and its species turnover and nestedness components, within each fire site and across all sites. Results indicated species turnover as the primary component of beta diversity within all communities. There was no trend of change with year-since-fire (YSF) in beta diversity among early post-fire communities, but beta diversity in the middle aged community was significantly higher. Species turnover patterns across fire sites revealed a weak dispersal limit effect, which was stronger at lower than upper slope position for woody plants, and reverse for herbs. At the site scale, the species dissimilarity and turnover both enlarged with increasing slope position difference, especially in the middle-aged community, but the species nestedness had no consistent trend among sites, except a decreasing trend in the middle-aged forest. (Partial) Mantel tests indicated habitat filtering (primarily indicating total nitrogen and slope position) played a much stronger role than dispersal limit and YSF (indicating competition intensity) for the post-fire forest assembly at the landscape scale, for both woody and herbaceous layers. However, at the site scale, Mantel tests indicated a diminishing effect of soil nutrient filtering with increasing YSF, while effects of topography and spatial distance in the middle aged community was stronger. This divergence suggests the primary assembly mechanism gradually shift from the soil constraint. While the seasonal drought and the mountain topography dominate the environmental legacy, our results imply that fires may reinforce a priority effect in the forests assembly in this region, by creating a habitat filtering (e.g. moisture and nitrogen limitation) effect on species composition in the post-fire communities.